Holocene environmental history of thermokarst lakes on Richards Island, Northwest Territories, Canada: Thecamoebians as paleolimnological indicators - Baltimore, A. (Audrey); Schroder-Adams, C. (Claudia); Dallimore, S.R. (Scott R.) (2000)
Richards Island, Northwest Territories, Canada, is characterized by thermokarst lakes which record Holocene limnological change. This study is the first report of thecamoebian assemblages and continuous annual lake water temperatures from these Arctic lakes. Ecological environments on Richards Island are influenced by a climatic gradient resulting from the contrasting influences of the cold Beaufort Sea to the north and the warm waters of the Mackenzie Delta to the east and west. This climatic gradient in turn influences modern thecamoebian assemblages, and is an indication of the complexity involved in interpreting past conditions from core material in this area. Population abundance and species diversity of thecamoebian assemblages on Richards Island are not significantly different from those reported from temperate and semi-tropical latitudes. However, certain assemblage characteristics, such as large and coarse agglutinated tests, dominance of assemblages by one or two species and low morphological variation are interpreted to be diagnostic of Arctic conditions. Thecamoebian assemblages in core material from the area indicate that the local paleolimnological conditions may have changed within the last 3 ka, and this is unrecorded in previously reported pollen data. Paleoenvironmental interpretations in a permafrost landscape have to take into account morphological instability of thermokarst lakes, which can be the cause of paleolimnological and consequently faunal change. In this area ecosystem development is clearly related to geomorphology and local climatic effects and is not exclusively controlled by regional climate change.